Antibiotic resistance of Streptococcus pneumoniae in Vietnamese children with severe pneumonia: a cross-sectional study - Tran-Quang, Khai; Nguyen-Thi-Dieu, Thuy; Tran-Do, Hung; Pham-Hung, Van; Nguyen-Vu, Trung; Tran-Xuan, Bach; Larsson, Mattias; Duong-Quy, Sy (Frontiers in Public Health, 2023)
Background: Streptococcus pneumonia is the most common bacteria causing community-acquired pneumonia (CAP) in children. The rate of S. pneumoniae resistance to antibiotics is increasing, especially in severe CAP. Therefore, the role of pathogenesis and the level of antibiotic resistance of S. pneumoniae causing severe CAP in children need regular updating and monitoring. Methods: It was a cross-sectional descriptive study. Nasopharyngeal aspiration specimens in children were cultured, isolated and identified for S. pneumoniae. Bacterial strains were assessed for antimicrobial susceptibility testing and determined for minimum inhibitory concentration (MIC). Results: 89 strains of S. pneumoniae were isolated from 239 severe CAP children. Bacteria were completely non-susceptible to penicillin (1.1% intermediate, 98.9% resistant), highly resistant to erythromycin (96.6%), trimethoprim/sulfamethoxazole (89.9%), clindamycin and clarithromycin (together 88.8%); the rates of sensitivity to chloramphenicol, levofloxacin, ciprofloxacin and ceftriaxone were 94.4%, 80.9%, 59.6% and 46.1%, respectively; 100% of strains were susceptible to vancomycin and linezolid. Trimethoprim/sulfamethoxazole, clindamycin, erythromycin, clarithromycin, vancomycin, linezolid with MIC50 coincided with MIC90 and equal to the CLSI resistance threshold; penicillin with MIC90 was 64 mg/L, 8 times higher than the CLSI resistance threshold; ceftriaxone with MIC90 was 6 mg/L, 1.5 times the CLSI resistance threshold. Conclusion: S. pneumoniae isolated were resistant to many types of antibiotics, including penicillin-resistant with high MICs. Therefore, the first choice of antibiotics should be ceftriaxone. Alternative antibiotics were levofloxacin, vancomycin and linezolid.